Implementasi model pembelajaran PJOK inovatif (IU-07-1) terhadap penigkatan hasil belajar siswa kelas VII di MTS al-kautsar talonang baru tahun 2022/2023 - Mohammad Zikri; Isyani; Jamaludin (Yayasan Baru Haji Samsudin, 2023)
The problem in this study is that it is found that the learning model used is less innovative. This causes students to be less motivated in learning so that the results obtained are not as expected. The purpose of this study was to determine the improvement of learning outcomes in long jump learning by using an innovative PJOK learning model (IU-07-1) to improve long jump learning outcomes in class VII students at MTs Al-Kautsar Talonang Baru. This research was conducted in two cycles, with each cycle consisting of planning, action implementation, observation, and reflection. Data analysis uses descriptive using percentage techniques. The initial condition before PTK was carried out, the students who were complete were 8 students or if it was percented as much as 32%. After cycle I was carried out, students who were complete increased by 13 students or 52%. In cycle II, it increased by 20 students or 80%. The conclusion of this study is that by using an innovative PJOK learning model (IU-07-1) can improve student learning outcomes in long jump learning for VII grade students of MTs Al-Kautsar Talonang Baru, West Sumbawa Regency in 2022/2023. This is evident from the results of learning completeness which is quite classical from cycle I to cycle II.